Bacterial and chemical leaching of chalcopyrite concentrates as affected by the redox potential and ferric/ferrous iron ratio at 22 degrees C - Bevilaqua, Denise [UNESP]; Lahti-Tommila, Heidi; Garcia, Oswaldo [UNESP]; Puhakka, Jaakko A.; Tuovinen, Olli H. (Elsevier B.V., 2014)
Biological oxidation of chalcopyrite by acidophilic and mesophilic bacteria becomes hindered over time due to passivation of the surface, making the mineral relatively recalcitrant to beneficiation in bioleaching processes. Several approaches have been discussed in the literature to overcome the passivation effect. The purpose of this work was to assess the effect of redox potential and Fe3+/Fe2+ ratios on the bioleaching of chalcopyrite in shake flasks. Two mixed cultures, three pure cultures of acidophiles, and two samples of chalcopyrite concentrates were used for this study. The initial redox levels between 350 and 600 mV were adjusted with Fe2+ and Fe3+ ratios, Sigma 200 mM and Sigma 300 mM Fe, at 0.33 and 2.5% pulp densities, respectively. In general, the differences in copper leaching were relatively minor among the test cultures and between the chemical controls and inoculated cultures. Copper dissolution increased linearly when the redox potential was in the 320-370 mV range, and this involved the inhibition of bacterial iron oxidation by the chalcopyrite sample. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Acidithiobacillus; Bioleaching; Chalcopyrite; Iron oxidation; Passivation